Scanning of β‐globin gene for identification of β‐thalassemia mutation in Romanian population - Talmaci, R. (J Cell Mol Med, 2007)
β‐Thalassemia is uncommon (0.5%) in the Romanian population, but it must be considered in the differential diagnosis of hypochromic anemia. The molecular characterization of β‐thalassemia is absolutely necessary for molecular diagnosis, as well as any genetic epidermiological study in this region. Molecular analyses consist of mutation detection by molecular scanning of β‐globin gene. This gene has 3 exons and 2 introns, involved in β‐thalassemic pathogenesis. Clinical application of DNA analysis on β‐thalassemic chromosomes allowed characterization of 29 persons with different β‐thalassemia mutations among 58 patients with anemia. The experimental strategy was based on sequential PCR amplification of most of the β‐globin gene and running on denaturing gradient gel electrophoresis of amplification products. Definitive characterization of mutations in samples identified with shifted DGGE patterns was performed ARMS‐PCR and/or PCR‐restriction enzyme analysis methods. Eight different β‐thalassemia alleles were identified, the most common being IVS I‐110 (G‐A) and cd 39 (C‐T). Comparison of overall frequency of mutations in the neighboring countries, shows that these results are in the frame of overall distribution of these mutations in Mediterranean area, especially in Greece and in Bulgaria. Molecular diagnosis is useful for differentiating mild from severe alleles, for genetic counseling, as well as for mutation definition in carriers, identified by hematological analysis necessary for prenatal testing and genetic counseling.